2001
DOI: 10.1172/jci11481
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor inhibits HIV-1 replication and is upregulated in placentae from nontransmitting women

Abstract: The placenta may play a critical role in inhibiting vertical transmission of HIV-1. Here we demonstrate that leukemia inhibitory factor (LIF) is a potent endogenous HIV-1-suppressive factor produced locally in placentae. In vitro, LIF exerted a potent, gp130-LIFRβ-dependent, HIV coreceptor-independent inhibition of HIV-1 replication with IC 50 values between 0.1 pg/ml and 0.7 pg/ml, depending on the HIV-1 isolate. LIF also inhibited HIV-1 in placenta and thymus tissues grown in ex vivo organ culture. The level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 43 publications
7
54
0
2
Order By: Relevance
“…These results agree with previous studies that have reported no association between the presence of the ∆32 allele and reduced risk of perinatally acquired HIV-1 infection (22,26,27). Other mechanisms proposed for the natural resistance to HIV-1 have included soluble factors with antiviral properties for preventing vertical transmission (28)(29)(30)32,33,54,55).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with previous studies that have reported no association between the presence of the ∆32 allele and reduced risk of perinatally acquired HIV-1 infection (22,26,27). Other mechanisms proposed for the natural resistance to HIV-1 have included soluble factors with antiviral properties for preventing vertical transmission (28)(29)(30)32,33,54,55).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the ∆32 mutation has not been found to confer protection against HIV-1 vertical transmission (22,26,27 response, have strong antiviral activity as a primary function or as a "collateral" effect. At least 5 factors have been identified in the maternal-fetus interface: stromal α-chemokine derived factor-1 (SDF-1) (28), leukemia inhibitory factor (LIF) (29), alloantigenstimulated factor (ASF) (30), RNases associated with human chorionic gonadotropin (hCG) (31)(32)(33) and, most recently, the β and α-defensins (34)(35)(36). Defensins are small cysteine-rich cationic peptides that exhibit antimicrobial activity against a broad spectrum of microorganisms (37).…”
mentioning
confidence: 99%
“…Nevertheless, the inhibitory activity of MDC is still controversial, and the mechanism through which MDC inhibits both R5 and X4 isolates also remains elusive Perez-Bercoff et al, 2003). Finally, LIF, a factor that can be released by CD4 + T cells, CD8 + T cells (Metcalf et al, 1990) and monocytes/macrophages (Anegon et al, 1991), inhibits HIV-1 in a tropismindependent manner and is produced at higher concentrations in placentae from nontransmitting HIV-infected women than in placentae from transmitting women (Patterson et al, 2001). Nevertheless, others factors undoubtedly constitute another important component of -MAF‖ activity.…”
Section: Macrophage Antiviral Factor "Maf"mentioning
confidence: 99%
“…Inversement, les femmes qui, infectées par le VIH, n'ont pas transmis le virus à leur nouveau-né, ont une concentration plus éle-vée de LIF [4]. En conséquence, il semble que les cytokines ou les facteurs de croissance, présents dans l'environnement placentaire et dont l'expression est modulée dans le temps, pourraient jouer un rôle important dans la régulation du cycle de réplication du VIH et la susceptibilité des trophoblastes au VIH.…”
Section: Rôle De L'environnement Placentaireunclassified
“…Par ailleurs, le risque de transmission augmente de 10% à 15% en cas d'allaitement [1]. Différents facteurs, d'origine maternelle ou virale, peuvent favoriser la transmission mère-enfant du VIH: la charge virale plasmatique, le nombre de lymphocytes T CD4 + , le stade plus ou moins avancé de l'infection par le VIH-1, la présence de maladies concomitantes, l'absence d'anticorps neutralisant le VIH, la malnutrition, ainsi que des facteurs génétiques tels que des mutations dans le corécepteur cellulaire du VIH, une faible production du facteur d'inhibition de la leucémie (LIF) et un polymorphisme HLA mère-enfant réduit [2][3][4]. Le phénotype viral est aussi à prendre en compte dans la transmission [5].…”
unclassified